Partisipasi Guru dan Orang Tua Dalam Menggalakkan Literasi Pada Kalangan Pelajar - Rialdo Rezeky Manogari (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The importance of literacy for students is not just being able to read and write but more than that. Literacy is the ability to use information and knowledge to increase intelligence according to change. One method that is tried to be carried out in response to the findings in research that has occurred a lot in the phenomenon of literacy in Indonesia is to carry out Community Service in the form of discussion and knowledge dissemination entitled